Cost-effective Diagnosis of Deep Vein Thrombosis and Pulmonary Embolism - Perrier, Arnaud; Bounameaux, Henri (Thrombosis and Haemostasis, 2001)
Suspected acute venous thromboembolism is a frequent and challenging clinical problem. Phlebography and pulmonary angiography are costly and invasive and, hence, ill-suited for diagnosing a disease present in only 20% of patients in whom it is suspected. Novel noninvasive instruments, such as plasma D-dimer measurement, lower limb compression ultrasonography and helical CT scan are important breakthroughs in the management of patients with suspected venous thromboembolism. However, none of these instruments is ideal, and they must be combined in rational and cost-effective diagnostic algorithms including clinical assessment, which is increasingly standardized. Such strategies must be validated in management studies, in which patients without venous thromboembolism are not treated and followed up during 3 months. Suspected massive pulmonary embolism is a distinct clinical situation requiring a specific diagnostic approach, in which echocardiography plays a major role. This paper reviews the performance of clinical evaluation and diagnostic tests for venous thromboembolism, and recently validated diagnostic schemes.
Keywords: Pulmonary embolism; deep vein thrombosis; diagnosis; cost-effectiveness analysis; outcome studies